REDUCING PAINFULNESS AND LABOR INTENSITY AND INCREASING ACCURACY OF TESTS IN NEEDLE ELECTROMYOGRAPHY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In Needle EMG measuring motor unit (MU) territory for neuromuscular system evaluation is used. Painfulness and traumaticity, labor intensity of the examination are regarded as serious disadvantages of needle EMG. The author offers a new needle electrode of telescopic construction, new methods and new parameters for evaluation of motor unit territory and neuromuscular system function. The new electrode significantly reduces labor intensity, painfulness and traumaticity of tests, new parameters enable to identify (evaluate) the density of motor units, crossing of motor unit territories and other characteristics of muscle. A significant reduction of painfulness and traumaticity of the examination will promote wide use of needle EMG possibly in pediatric patients as well. New methods and parameters enable better evaluation of functional state of motor units and neuromuscular system.